Impact of Venezuelan migration on the informal workforce of native workers in Colombia - William Prieto Bustos; Cristian Darío Castillo Robayo; Jacobo Campo Robledo; Juliana Molina Dominguez (Economies, 2023)
Colombia experienced a substantial increase in annual migration flow from Venezuela from 2013 to 2019, accumulating 1.7 million migrants by the end of 2019. According to migration data, 2016 was a breaking point in migration growth, with an increase of 137.57% compared with 2015 and at which time the influx of migrant workers began to be massive, rapid, and involuntary. In this regard, the research paper investigates, using a difference-in-differences model, the impacts on the labor market across different definitions of the informal workforce, testing the hypothesis that short-term labor migration increased (1) the number of employed individuals in companies with a workforce of fewer than five people, (2) the number of employed individuals not contributing to the social security system, and (3) the relative participation of the informal workforce in total employment from 2015 to 2018. The main results indicate an expansion in the labor market's informal segment, increasing the number of non-returned native workers in the informal workforce without significant increases in the participation of informality in total employment. The results remain robust across various samples in models adjusted for departmental-, municipal-, and individual-level data. Following the economic theory, the research findings seem to follow a transmission mechanism in which migrant workers reduce labor costs and increase production in informal markets, providing better conditions to increase informal jobs for native workers. Several national and international stakeholders implementing income-generation alternatives in the border departments focusing on migrant employment services could find the research findings helpful in at least two aspects: (1) fighting cultural stereotypes upon which basis native workers tend to see migration as a threat to their current job holdings requires evidence that shows migrant workers contribute to economic growth and employment; (2) promoting better public policies to take advantage of initial conditions that favor labor integration of migrant workers such as cultural and language similarities among natives and migrants works better when there is evidence of the migration's positive impacts.
Keywords: 330; migration; labor markets; informal workforce labor markets